The Joshua generation: Israeli occupation and the Bible - Havrelock, Rachel S. (Princeton University Press, 2020)
Frontmatter -- Contents -- Illustrations -- Acknowledgments -- Introduction. Endless War -- 1. The Conquest of Land and Language -- 2. “So Very Much Left to Conquer” and the Persistence of the Local -- 3. The Joshua Study Group at the Home of David Ben-Gurion -- 4. The Tribes of Joshua Land -- Conclusion. End This War -- Index